Penerapan Media Pembelajaran Kahoot Dalam Meningkatkan Minat Belajar IPA Peserta Didik Kelas IX SMP Negeri 2 Sumber - Nurwanti Fatnah; Hasanuddin, Nurul Hikmah; Adiyanti (LPPM Institut Pendidikan Nusantara Global, 2025)
This study investigates the effectiveness of Kahoot as a digital learning medium in enhancing students’ interest in science education. Conducted at SMP Negeri 2 Sumber in class IX F, the research utilized a Classroom Action Research (CAR) design implemented over two cycles, each comprising planning, implementation, observation, and reflection phases. The participants included 32 ninth-grade students. Data collection methods consisted of classroom observation, questionnaires, interviews, and document analysis. Quantitative descriptive analysis was performed using a Likert scale. The findings revealed a substantial increase in students' interest in learning, with scores rising from 53% in the pre-cycle (classified as low), to 68% in Cycle I (moderate), and reaching 83% in Cycle II (high). Improvements were observed across all dimensions of learning interest: enjoyment, curiosity, engagement, and attention. The integration of Kahoot fostered an interactive and enjoyable learning environment, which significantly motivated students to participate more actively in the classroom. These results suggest that Kahoot serves as an effective and innovative pedagogical tool for enhancing student engagement and improving the overall quality of science education at the secondary level.